Telemedicine for evaluation of brain function by a metacomputer. - Mizuno-Matsumoto, Y. (IEEE Transactions on information technology in biomedicine)
A method of evaluating brain function using the metacomputer concept of the Globus system combined with the Message Passing Interface (MPI) is described. The proposed method has the ability to exploit various geographically distributed resources and parallel computing linked to a high-technology medical instrumentation system (magnetoencephalography) to analyze the functional state of the brain. It is envisaged that the method will lead to the realization of an efficient telemedicine system for health care.